2018
DOI: 10.1002/anie.201802385
|View full text |Cite
|
Sign up to set email alerts
|

Accessing Frustrated Lewis Pair Chemistry from a Spectroscopically Stable and Classical Lewis Acid‐Base Adduct

Abstract: B(C F ) and P(MeNCH CH ) N form a classical Lewis adduct, (C F ) BP(MeNCH CH ) N. Although (C F ) BP(MeNCH CH ) N does not exhibit spectroscopic evidence of dissociation into its constituent acid and base, products of frustrated Lewis pair (FLP) addition reactions are seen with PhNCO, PhCH N , PhNSO, and CO . Computational studies show that thermal access to the dissociated acid and base permits FLP reactivity to proceed. These results demonstrate that FLP reactivity extends across the entire continuum of equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 38 publications
(43 reference statements)
3
53
0
Order By: Relevance
“…Very recently, Stephan and colleagues interrogated the dissociation of 141 a (Scheme ) by using long mixing time 19 F‐ 19 F EXSY in the presence of a triarylborane component. The complete NMR silence of the exchange process indicates the rather high stability of the FLP 141 a .…”
Section: Nucleophile–electrophile Reactionsmentioning
confidence: 99%
“…Very recently, Stephan and colleagues interrogated the dissociation of 141 a (Scheme ) by using long mixing time 19 F‐ 19 F EXSY in the presence of a triarylborane component. The complete NMR silence of the exchange process indicates the rather high stability of the FLP 141 a .…”
Section: Nucleophile–electrophile Reactionsmentioning
confidence: 99%
“…[50] 2 Ph :c olorless crystals, C 27 H 35 BN 3 P, M r = 443.36, crystal size 0.20 0.10 0.06 mm, orthorhombic, space group Pca2 1 (no.29), a = 20.3505(5), b = 18.8682(5), c = 12.8093(3) , V = 4918.5(2) 3 , Z = 8, 1 = 1.197 Mg m À1À3 , m(Cu-K a ) = 1.12 mm À1 , F(000) = 1904, 2q max = 144.08,3 6741 reflections, of which 9434 were independent (R int = 0.039), 578 parameters, 1r estraint, R1 = 0.034 (for 8901 I > 2s(I)), wR2 = 0.086 (all data), S = 1.03, largest diff. peak/hole = 0.30/ À0.22 e À3 , x = 0,452 (17). 3 t Bu :c olorless crystals, C 25 H 39 BN 3 P, M r = 423.37, crystal size 0.22 0.08 0.06 mm, monoclinic, space group P2 1 /n (no.14), a = 8.8381 (6), b = 14.9452(9), c = 19.3839 (12) , b = 102.622(2)8, V = 2498.5 (3) 3 , Z = 4, 1 = 1.126 Mg m À1À3 , m(Mo-K a ) = 0.13 mm À1 , F(000) = 920, 2q max = 55.28,4 9835 reflections, of which 5768 were independent (R int = 0.040), 272 parameters, R1 = 0.045 (for 4845 I > 2s(I)), wR2 = 0.113 (all data), S = 1.05, largest diff.…”
Section: X-ray Crystal Structure Determinationsmentioning
confidence: 99%
“…Phosphorus/boron-based FLPs have been shown to add to the a-nitrogen of the azide form-ing coordinationm ode D (Figure 1) [14] and, in one case, it was found that upon irradiation this speciesr earranges to a,b-nitrogen adduct E. [15] The a,g-nitrogen coordinationm ode F was found by treatingageminal FLP with mesityl azide. [16,17] In analogy to the reactivityo fN HCs (C;F igure 1), dinitrogen elimination occurs when TMS azide was reacted with aP /Al-based FLP affording heterocycle G, [18] yet in this case no follow-up chemistry has been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Of growing interest is the development of FLPs in which transition-metals pecies appear as one of the components [8d,f, 9] with the aim of combining the powerful cooperative main-group FLP reactivity with the rich transition-metal chemistry.F or some FLP systems, the equilibrium between the dissociateda cid and base and the classical Lewis acid/base adduct was detected.I nterestingly,F LP reactivity has been observed even when the equilibrium wasa lmostc ompletely shiftedt oward the classical Lewis acid/base adduct, providedt hat the dissociated state was thermally accessible. [10] For this reactivity the concept of "thermally inducedf rustration" was introduced [11] and the terms "masked" [12] and" dormant" [13] have been used to describe the involved FLPs.…”
mentioning
confidence: 99%